Eurosensors 2018 2018
DOI: 10.3390/proceedings2130996
|View full text |Cite
|
Sign up to set email alerts
|

Array of MOX Nanowire Gas Sensors for Wastewater Management

Abstract: Water is a common fundamental resource for life. The effects of climate change, pollution and waste make it an increasingly scarce resource. Therefore, it becomes very important to monitor water quality to identify situations of possible harm to humans. In this study, incoming wastewater of the depuration plant of A2A Ciclo Idrico in Brescia has been analyzed with an array of MOX nanowire gas sensors. In addition, GC-MS technique has been used to relate sensors responses with the emitted VOCs of the samples. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…In the course of the analysis of measurement data from the samples of water by means of an enose, it was observed that each of the employed statistical methods (Figures 4-7 The observations from primary settling tank and secondary settling tank depicted in Figure 5 were separable, and certain directions of changes which took place in the wastewater treatment process observed in PCA map could be defined. Based on the PCA and the distribution of ellipses on the graph, certain tendencies and correlations between the pollution indicators could be observed, which has already been mentioned in the literature [7,8,11,[14][15][16]60]. Moreover, based on previous research conducted in a laboratory bioreactor [12], a shift in the characteristics of the considered samples towards the positive values on the x-axis was observed, along with an increasing wastewater pollution level [61].…”
Section: Resultssupporting
confidence: 54%
“…In the course of the analysis of measurement data from the samples of water by means of an enose, it was observed that each of the employed statistical methods (Figures 4-7 The observations from primary settling tank and secondary settling tank depicted in Figure 5 were separable, and certain directions of changes which took place in the wastewater treatment process observed in PCA map could be defined. Based on the PCA and the distribution of ellipses on the graph, certain tendencies and correlations between the pollution indicators could be observed, which has already been mentioned in the literature [7,8,11,[14][15][16]60]. Moreover, based on previous research conducted in a laboratory bioreactor [12], a shift in the characteristics of the considered samples towards the positive values on the x-axis was observed, along with an increasing wastewater pollution level [61].…”
Section: Resultssupporting
confidence: 54%
“…The drinking water is, however, exposed to permanent threats due to the uncontrollable release of industrial wastes, which can result in microbial storms. In this context, frequent evaluation of the quality of water and the precise management of water resources are essential factors to ensure the supply of clean and safe water for humans [ 185 ] and the determination of the microbiological and chemical contamination [ 186 ]. The daily activity of humans has led to the discharge of a huge amount of pollutants into the environment including the seas and oceans which can seriously threaten marine life, causing continuous destruction of the oceans and seas as well as the shores [ 187 ].…”
Section: Application Of Moxs E-noses For Environmental Monitoringmentioning
confidence: 99%
“…In [ 186 ], the use of metal oxide gas sensors embedded in an array for analysis of the complex volatile fingerprint of the water and wastewater samples was investigated. The gas chromatography technique along with solid-phase microextraction was employed as a reference method for a better understanding of the responses of the sensors and their relationships with a specific class of VOCs.…”
Section: Application Of Moxs E-noses For Environmental Monitoringmentioning
confidence: 99%